빛간섭단층혈관조영술을 이용한 단안 정상안압녹내장에서의 망막모세혈관 분석 - 조창우(Chang Woo Cho); 정우현(Woo Hyun Jung); 김정림(Jung Lim Kim) (Daihan angwa haghoi jabji, 2021)
목적: 단안 정상안압녹내장 환자의 이환안 및 반대안과 정상 대조군에서 빛간섭단층혈관조영술을 이용, 망막모세혈관 인자를 분석, 비교했다. 대상과 방법: 단안 정상안압녹내장 이환안 및 반대안군 각 24안과 정상 대조군 29안의 시신경유두주변부, 황반부의 혈관밀도, 관류밀도를 빛간섭단층혈관조영술을 통해 측정, 분석했다. 결과: 표층모세혈관총에서, 정상안압녹내장의 반대안군에서 정상 대조군에 비해 황반부 내측 중 하측 영역 혈관밀도 및 내측 중 하측 영역, 외측 영역 평균 관류밀도 감소를 보였고(p=0.008, p<0.001, p=0.001), 이환안군은 반대안 및 정상 대조군보다 시신경유두주변부 전체, 내측 평균, 내측 중 하측, 외측 중 하측, 황반부 외측 중 하측 영역 혈관밀도(p=0.014, p=0.011, p<0.001, p<0.001, p<0.001) 및 관류밀도 감소(p=0.017, p=0.023, p<0.001, p=0.001, p<0.001), 시신경유두주변부 외측 평균 영역 혈관밀도 감소(p=0.010)를 보였으며, 정상 대조군보다 시신경유두주변부 외층 평균 영역 관류밀도 감소(p=0.003), 황반부 전체, 내측 중 하측, 외측 평균 영역 혈관밀도(p=0.041, p=0.008, p=0.006) 및 관류밀도 감소(p=0.013, p<0.001, p=0.001), 황반부 외측 중 이측 영역 관류밀도 감소(p=0.003) 를 보였다. 황반부 심층모세혈관총의 유의한 차이는 없었다. 결론: 단안 정상안압녹내장 이환안 및 반대안에서 빛간섭단층혈관조영술을 이용한 망막모세혈관 인자의 확인이 유용할 것으로 생각된다. Purpose: The purpose of this study was to analyze retinal capillary parameters using optical coherence tomography angiography (OCTA) of the affected eye and the fellow eye of unilateral normal tension glaucoma (NTG) patients and compare the findings with eyes from a normal control group. Methods: A retrospective cross-sectional study was carried out on patients diagnosed with unilateral NTG (24 affected eyes and 24 fellow eyes each) and normal individuals (29 eyes, the control group). OCTA was used to measure the vascular density (VD) and perfusion density (PD) of the macular area and the peripapillary area. Results: In the superficial capillary plexus, the fellow eye group of unilateral NTG patients showed a decrease in VD of the inner- inferior and PD of the inner-inferior and outer-average peripapillary area, compared with the normal control group (p = 0.008, p < 0.001, and p = 0.001). In the affected NTG eye group, the VD (p = 0.014, p = 0.011, p < 0.001, p < 0.001, and p < 0.001) and PD (p = 0.017, p = 0.023, p < 0.001, p = 0.001, and p < 0.001) of the total, inner-average, inner-inferior, and outer-inferior peripapillary area, and the outer-inferior macular area decreased compared to the fellow eye and normal control group, as well as the VD of the outer-average peripapillary area (p = 0.010). The PD of the outer-average peripapillary area (p = 0.003); the VD (p = 0.041, p = 0.008, p = 0.006) and the PD (p = 0.013, p < 0.001, p = 0.001) of the total, inner-inferior, and outer-average macular area; and the PD of the outer-temporal macular area (p = 0.003) were lower than the normal control group. There was no difference in the VD or PD obtained from the deep capillary plexus of the macular area among the groups. Conclusions: It is useful to observe retinal capillary parameters using OCTA for patients with unilateral NTG. KCI Citation Count: 0